FEATURES OF GROWTH AND DEVELOPMENT OF SOYBEAN PLANTS DEPENDING ON THE VARIETY AND CULTIVATION TECHNOLOGY ELEMENTS - Fedoruk , I.V.; Khmelianchyshyn , Y.V.; Horodyska , O.P. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
The article reflects the results of studies carried out during 2015-2018 on the influence of cultivation technology elements, the peculiarities of the growth processes and soybean plants development of foreign varieties. Choosing the right variety depends on market requirements and the grower needs. The most attractive varieties of soybeans are capable of providing cost-effective yield and cultivation flexibility under various technologies. The main evaluation criteria when choosing a variety are productivity, duration of the growing season, resistance to shedding and lodging, resistance to diseases and pests, the ability to adapt to specific soil and climatic conditions; also, when choosing, it is necessary to pay attention to the nutritional properties - the protein content directly affects the grown products cost. The formation of a soybean crop is an extremely complex process in which a large number of factors are involved. The growth peculiarities and development of such leguminous crops as soybeans provide for slight adjustments to the yield due to the number of stems, for example, early-ripening varieties require a much greater plant density per m2, since such plants are not fully capable of branching, and in mid- and late-ripening varieties, this property is expressed much better, which is associated with the consistent and long-term differentiation of generative organs and, as a consequence, the dependence of these processes on growing conditions and the negative factors influence. Under the agrometeorological factors influence, the duration of the growing season of soybean plants changes, and these factors, as a result, affect the individual phases length of growth and development of soybeans